Recent Progresses and Prospects of Cathode Materials for Non-aqueous Potassium-Ion Batteries - Zhu, Yun-Hai; Yang, Xu; Sun, Tao; Wang, Sai; Zhao, Yin-Lei; Yan, Jun-Min; Zhang, Xin-Bo (Electrochemical energy reviews, 2018)
Rechargeable potassium-ion batteries (KIBs) are potential alternatives to lithium-ion batteries for application in large-scale energy storage systems due to their inexpensive and highly abundant resources. Recently, various anode materials have been investigated for use in KIBs, especially the traditional graphite anodes which have already been successfully applied in KIBs. In contrast, the appropriate cathode materials which are able to accommodate large K ions are urgently needed. In this review, a comprehensive summary of the latest advancements in cathode materials for non-aqueous KIBs in terms of capacity, cycle life and energy density will be presented, as well as K-storage mechanisms. In addition, various strategies to improve K-storage performance will be provided through combining insights from the study of material structures and properties and thus bring low-cost non-aqueous KIBs a step closer to application in sustainable large-scale energy storage systems. Graphical Abstract